Five-Factor Model and DSM-5 Alternative Model of Personality Disorder Profile Construction: Associations with Cognitive Ability and Clinical Symptoms - Chloe Lau; R. Michael Bagby; Bruce G. Pollock; Lena Quilty (Journal of Intelligence, 2023)
Although numerous studies have explored latent profiles using the Five-Factor Model (FFM) of normative personality, no studies have investigated how broad personality traits (i.e., FFM) and pathological personality traits using the alternative model of personality disorder (AMPD) may combine for latent personality profiles. The present study recruited outpatients (N = 201) who completed the Big Five Aspects Scales (BFAS), Personality Inventory for DSM-5 (PID-5), Structured Clinical Interview for DSM-IV (SCID-I/P), gambling and alcohol use measures, and the Weschler Intelligence subtests. When FFM and AMPD measures were combined, latent profile analyses revealed four profiles, Internalizing-Thought disorder, Externalizing, Average-Detached, and Adaptive. Detachment and openness to experience were the most and least essential traits for profile distinction, respectively. No associations between group membership and cognitive ability measures were found. Internalizing-Thought disorder membership was linked with a current mood and anxiety disorder diagnosis. Externalizing profile membership was associated with younger age, problematic gambling, alcohol use, and a current substance use disorder diagnosis. The four FFM–AMPD profiles overlapped with the four FFM-only and three AMPD-only profiles. Overall, the FFM–AMPD profiles appeared to have better convergent and discriminant validity with DSM-relevant psychopathology.